2018
DOI: 10.1002/lary.27296
|View full text |Cite
|
Sign up to set email alerts
|

Initial presentation of human papillomavirus‐related head and neck cancer: A retrospective review

Abstract: 4. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…This result was unexpected, given that HPVrelated OPSCC is classically associated with sexual activity, and most Middle Eastern countries are historically more conservative [6]. However, the patient profile of our study sample generally fits that of an HPV-related patient as described in the literature [6][7][8]. Most HPVrelated patients in our study were males who presented with nodal metastases and advanced stage at diagnosis.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This result was unexpected, given that HPVrelated OPSCC is classically associated with sexual activity, and most Middle Eastern countries are historically more conservative [6]. However, the patient profile of our study sample generally fits that of an HPV-related patient as described in the literature [6][7][8]. Most HPVrelated patients in our study were males who presented with nodal metastases and advanced stage at diagnosis.…”
Section: Discussionmentioning
confidence: 56%
“…An important aspect of our study will be its impact on health education and on raising awareness about HPV-related OPSCC, which could play a role in controlling the increasing prevalence of this entity and promoting vaccination among young adults. With the advent of vaccines for prevention of HPV-related cervical cancer, the incidence of HPV-related OPSCC might decrease with the decrease of HPV-positivity and transmission as a whole [8]. However, a recent study conducted in Lebanon found an HPV vaccination uptake rate of 2.5% and a rate of awareness about HPV infection of 34% amongst mothers of schoolgirls in their sample [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide [1]. In the last few decades, there has been an increase in the incidence of oropharyngeal squamous cell carcinoma (OPSCC) related to human papilloma virus (HPV), a distinct entity from the traditional tobacco-and alcohol-related OPSCC [2].…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective analysis of 207 patients with OPSCC found that patients with HPV-positive OPSCC were most likely to present with a neck mass (56%), sore throat (11%), or oral mass (11%). 14 Furthermore most HPV-positive patients in this study presented at a tumor, node, metastasis stage of IVa (57%), with the tonsil (60%) and base of tongue (40%) being the most common primary tumor site. 14 If a patient presents to the office with a history suspicious for OPSCC, it is recommended that providers conduct a formal head and neck examination that includes inspection of the oral cavity, palatine tonsils, base of tongue, and cervical lymph nodes.…”
Section: Screening and Presentationmentioning
confidence: 72%